EFFECT OF DEHYDRATION IN LACTATING WOMEN ON BREAST MILK PRODUCTION AND INFANT GROWTH - Mirsagatova M. R.; Jalolov N. N (Web of Journals Publishing, 2025)
The aim of this article is to analyze the effects of dehydration in lactating women on breast milk production and the resulting consequences for infant growth. The authors summarize evidence from existing literature, epidemiological data, and clinical studies regarding fluid-intake patterns, physiological mechanisms, the impact on milk composition, and associations with infant weight gain and growth indicators. The findings suggest that the relationship between maternal hydration status and milk production is complex, and that general recommendations should be combined with individualized counseling. (Primary sources include recent review articles and systematic analyses).
Keywords: Breastfeeding, dehydration, maternal hydration, breast milk, milk volume, infant growth, lactation.